1986
DOI: 10.1126/science.3010463
|View full text |Cite
|
Sign up to set email alerts
|

AIDS Retrovirus Induced Cytopathology: Giant Cell Formation and Involvement of CD4 antigen

Abstract: The formation of multinucleated giant cells with progression to cell death is a characteristic manifestation of the cytopathology induced by the AIDS retrovirus in infected T lymphoid cells. The mechanism of giant cell formation was studied in the CD4 (T4/Leu 3) positive T cell lines JM (Jurkat) and VB and in variants of these lines that are negative for cell surface CD4 antigen. By means of a two-color fluorescent labeling technique, multinucleated giant cells in infected cultures were shown to form through c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
197
1
8

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(208 citation statements)
references
References 23 publications
2
197
1
8
Order By: Relevance
“…15,[47][48][49][50] A positive correlation between CD4 þ T cell decline and infection by syncytium-inducing HIV-1 or SIV-1 variants has been established in vitro 15,20,48,51 and, more importantly, in vivo, in humans with AIDS, 47,49 humanized SCID mice, 52 and monkeys. 53 We have studied several in vitro models of syncytial apoptosis, in particular a coculture system involving HeLa cells transfected with the HIV-1 LAI Env gene and HeLa cells transfected with CD4.…”
Section: Syncytial Apoptosis Induced By Envmentioning
confidence: 98%
“…15,[47][48][49][50] A positive correlation between CD4 þ T cell decline and infection by syncytium-inducing HIV-1 or SIV-1 variants has been established in vitro 15,20,48,51 and, more importantly, in vivo, in humans with AIDS, 47,49 humanized SCID mice, 52 and monkeys. 53 We have studied several in vitro models of syncytial apoptosis, in particular a coculture system involving HeLa cells transfected with the HIV-1 LAI Env gene and HeLa cells transfected with CD4.…”
Section: Syncytial Apoptosis Induced By Envmentioning
confidence: 98%
“…Also HIV-1-infected CD4 + lymphocytes form giant cells in vitro, but until now, they have not been observed in AIDS patients. Other mechanisms could account for the remaining MGCs formed with Dnef-HIV-1-infected macrophages (53,(66)(67)(68)(69)(70) [i.e., fusion of HIV-1 infected T cells is in part mediated by interaction of the virally encoded env gene expressed at the plasma membranes of infected cells with CD4 receptors (66,67,(71)(72)(73)(74)(75)]. Because giant macrophages rapidly form upon expression of Nef alone, it indicates that Nef is sufficient to trigger macrophage fusion independently of Env or other viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This apoptosis is characterized by the translocation of Bax from the cytosol to mitochondria leading to the mitochondrial membrane permeabilization with loss of the DC m ), release of apoptogenic intermembrane proteins, in particular apoptosis-inducing factor and cytochrome c, caspase activation, and nuclear chromatin condensation. 136 In vitro studies have also identified a positive correlation between CD4 T-cell depletion and infection by syncytium inducing HIV-1 137,138 or SIV variants. 75,[139][140][141] In addition, multinucleated giant cells, a pathological hallmark of AIDS encephalopathy are also found during SIV-encephalitis 142,143 and these cells revealed DNA fragmentation.…”
Section: Cell Cycle Dysregulationmentioning
confidence: 99%